Globalization Policies And E-Commerce Impact On Iranian Information Technology SME Sector - Rahimi, Mohammad (2011)
The purpose and aim of this study is to realize and identify globalization policies and electronic commerce impact on Iranian information technology in the SME sector. A study was undertaken in Iran by the researchers and examiners who provided a considerable and important context for the research. This research is conducted along with Iranian SMEs in consequence of shortage in studies about export development of SMEs and a shortage of published from the e-commerce point of view.